Elektrokardiografie vcera a dnes - Kölbel, F (Casopis lekaru ceskych, 2009)
Electrocardiography is one of most classical methods of examination in medicine and in cardiology. After more than 100 years of practical use, it is indispensable in diagnosing arrhythmias as well as several, clinically important proarrhythmic states. In those, the heart with normal anatomy endangers the patient with the risk of serious, frequently life threatening arrhythmias (Long QT Syndrome, Brugada Syndrome, Wolff-Parkinson-White Syndrome, T-wave alternans). Further, electrocardiography is nowadays important in diagnosing the very fresh signs of myocardial ischemia. Present time electrocardiography is demanding for manufacturers of electrocardiographic machines, and requires precise, standard technique of examination. Despite automatic evaluation programmes of electrocardiogram, which are nowadays almost a standard, physicians should understand well the electrocardiogram, and must be able to correct frequent inaccuracies of the automatic evaluations.
Keywords: elektrokardiografie; Electrocardiography; Cardiomegaly; Humans; kardiomegalie; srdeční arytmie; Arrhythmias, Cardiac; lidé